Investigating the Educational Problems of High School Students in Virtual Education During the Outbreak of Covid 19 - Karimi Baghmalek, Ayatollah (International Journal of Education and Cognitive Sciences, 2022)
The purpose of this study was to investigating the educational problems of high school students in virtual education during the outbreak of Covid 19 in Khuzestan province.310 students were selected in a multi-stage cluster sampling and the most important problems were identified by descriptive method of exploratory factor analysis with the help of SPSS software version 21.The results showed that six factors (absentee communication in the virtual classroom, lack of sufficient coercion and responsibility to do work, school and teacher characteristics, lack of social interaction, stress on families and limitations in teaching courses) contains38 items with 89.32% of total of variance.It is suggested that these problems be reduced by holding training courses and empowering students, teachers and parents and providing the appropriate internet network and the necessary software and tools.It is suggested that these problems be reduced by holding training courses and empowering students, teachers and parents and providing the appropriate internet network and the necessary software and tools.